Sustainability and Public Policies: Treatment in Contemporary Environmental Education (Research, Society and Development, 2020)
The focus study aims to explore the correspondences between the applications of public policies and sustainability, through a theoretical review, as the condition by which this conceptual theme directs the treatment in contemporary environmental education. The methodology used to achieve this objective was qualitative of a descriptive nature, due to the use of a theoretical exam of analytical specificity on sustainability and public policies: the treatment in environmental education in contemporary times. When calculating the results, the situation of loss of the integration potential of the industrial society was found, all that protection understood by the Welfare State revealed a set of uncertainties and mistrust. It was possible to identify a double difficulty: to stipulate a set of citizen actions that link this education to the broader objective of public policies and to rescue the idea of sustainability as a vehicle for socio-political expression.